2002
DOI: 10.1074/jbc.m105697200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Phosphatidylserine Binding Sites to Structural Domains of Factor Xa

Abstract: Binding of short chain phosphatidylserine (C6PS) enhances the proteolytic activity of factor X a by 60-fold (Koppaka, V., Wang, J., Banerjee, M., and Lentz, B. R. (1996) Biochemistry 35, 7482-7491). In the present study, we locate three C6PS binding sites to different domains of factor X a using a combination of activity, circular dichroism, fluorescence, and equilibrium dialysis measurements on proteolytic and biosynthetic fragments of factor X a . Our results demonstrate that the structural responses of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
90
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(101 citation statements)
references
References 48 publications
10
90
1
Order By: Relevance
“…This makes it very unlikely that very small and hydrodynamically undetectable C6PS aggregates could explain our observations. The second, and even stronger, argument against this possibility is provided by the observations that only two and four C6PS molecules were bound at saturation per FX a and FV a , respectively (10,32). This small amount of lipid could not form even a local surface for the binding of these proteins, and we must conclude that specific sites on both FX a and FV a bind C6PS in a way that regulates the structure, function, and assembly of the components of the prothrombinase complex.…”
Section: Activation Of Meizothrombin To Thrombin In the Presence Of Fmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes it very unlikely that very small and hydrodynamically undetectable C6PS aggregates could explain our observations. The second, and even stronger, argument against this possibility is provided by the observations that only two and four C6PS molecules were bound at saturation per FX a and FV a , respectively (10,32). This small amount of lipid could not form even a local surface for the binding of these proteins, and we must conclude that specific sites on both FX a and FV a bind C6PS in a way that regulates the structure, function, and assembly of the components of the prothrombinase complex.…”
Section: Activation Of Meizothrombin To Thrombin In the Presence Of Fmentioning
confidence: 99%
“…At first glance, this is quite surprising, but it is actually not an unreasonable possibility, because we have shown that binding of C6PS to the second FX a site competes with synthetic substrate binding to the active site of FX a (32). Although this does not seem to interfere with the FX a proteolytic activity in the absence of FV a (8), 2 our results indicate that C6PS binding to the second site on FX a bound to FV a2 may interfere with formation of a productive enzymesubstrate complex.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This could be explained by C6PE binding to two linked sites, as has been reported for C6PS (41). Our current hypothesis is that C6PS and C6PE share the regulatory site on Xa (non-additive effects on activity) but also bind to the anomalous site in the catalytic domain to which the regulatory site is linked (41). More extensive experiments are needed to prove this hypothesis.…”
Section: Discussionmentioning
confidence: 85%
“…In this picture, the effect of PE on membrane interfacial packing contributes only to bringing factor Va to the membrane, but not for the reduction in K m , the increase in k cat , and the decrease in K d app , which result from PE regulation of both factors Xa and Va. The lipid-binding regions through which C6PS influences factors Va and Xa have been identified (14,27,41). Are these the same sites occupied by PE?…”
Section: Discussionmentioning
confidence: 99%